1979
DOI: 10.1111/j.1749-7345.1979.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Length‐weight Relations for Several Species of Penaeid Shrimp Cultured in Ponds Near Corpus Christi, Texas

Abstract: Length measurements are relatively easier to obtain than weight measurements. Length‐weight relationships provide a means of estimating weight based on length. Linear regressions using the model W = aLb were calculated from paired length and weight measurements (1972 through 1979) of Penaeus duorarum, P. occidentalis, P. setiferus, P. stylirostris, and P. vannamei cultured at the Texas A&M Shrimp Mariculture facility near Corpus Christi, Texas. Length‐frequency distributions and regression formulae for predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The calculated effect size corresponds to comparison data of the performance of non‐native species, in relation to native ones, in the U.S.A (Hutchins et al . ; Sandifer et al . ; Williams et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The calculated effect size corresponds to comparison data of the performance of non‐native species, in relation to native ones, in the U.S.A (Hutchins et al . ; Sandifer et al . ; Williams et al .…”
Section: Resultsmentioning
confidence: 99%
“…Only seven of the selected papers contained all the needed information. The calculated effect size corresponds to comparison data of the performance of non-native species, in relation to native ones, in the U.S.A (Hutchins et al 1979;Sandifer et al 1993;Williams et al 1996); Thailand and Vietnam (Limhang et al 2005;Boyd et al 2017); Mexico (Rosas et al 2001) and Brazil (Peixoto et al 2003) (Table 3). As it may be seen, of the 22 studies analysed, 19 of them showed a positive effect of the use of non-native over native species and only in three of them (studies 2, 3 and 4), the observed effect was the opposite.…”
Section: Meta-analysiseffect Sizementioning
confidence: 92%
See 2 more Smart Citations
“…On the other hand, there are studies on F. duorarum weight-length relationships (Kutkuhn, 1962;Fontaine & Neal, 1971;Hutchins, Chamberlain, & Parker, 1979;Pérez-Castañeda & Defeo, 2001), but most of them are based on commercial fisheries or aquaculture activities, and thereby do not always take into account the small juvenile stages in the results. Information in this sense is important, to know the biological characteristics of recruits, juveniles, and subadults in the natural nursery areas, and could help to understand migration in this part of the life cycle of the pink shrimp.…”
mentioning
confidence: 99%